Study of Proximate and Nutritional Composition of Leaves of Grewia tiliaefolia Vahl - Rajesh Kumar Vaspri (Journal of Global Pharma Technology, 2019)
ABSTRACTObjective: The present study was aimed to assess nutritional value of the leaf of Grewia tiliaefolia Vahl belonging to the family tiliaceae. The parameters included proximate analysis of the leaves of Grewia tiliaefolia Vahl for carbohydrates, proteins, moisture, ash, and crude fiber. The determination of minerals of the leaves of the plant were magnesium, calcium, copper, iron, zinc, sodium and potassium. Methods: The methods employed for determination of proximate and nutritional value of leaf of Grewia tiliaefolia was according to standard procedures (AOAC). The instrument used was spectrophotometer. Results and conclusion: The results concluded that the proximate analysis of Grewia tiliaefolia Vahl leaf showed presence of carbohydrates, proteins, moisture, ash and crude fiber. Mineral contents like calcium, magnisium iron, zinc, copper, sodium, potassium was present. It is concluded that leaves of this plant is rich in nutritional components. Keywords--- Grewia tiliaefolia Vahl, Proximate analysis, Minerals, AOAC, Spectrophotometer.